USABILITY APLIKASI RMS BOOKING BERBASIS WEB DENGAN METODE IMPORTANCE PERFORMANCE ANALYSIS. - Wiliani, Ninuk; Endang; Fitria; Rachmalia Feta, Neneng (Universitas Siber Indonesia, 2024)
Online booking service will make it easier for users to rent meeting rooms, so that it can be done more efficiently in time and place, Bank BRI provides online booking facilities, namely RMS booking. Use can make it easier for users, especially the board of directors who want to use the room for meetings. The purpose of this study is to identify what indicators need to be improved based on the importance of performance analysis. The identification results show that there are no attributes in quadrant I